(untitled) (Research, Society and Development, 2021)
Objective: to identify the microorganisms present in chronic vasculogenic, diabetic and pressure lesions for the control of wound infections. Methodology: Quantitative, exploratory and descriptive study in a large public and teaching hospital. Swabs and biopsies were performed on patients registered at a wound clinic. Through the result of the microbiological analysis, the microorganisms were separated according to the incidence values according to the etiology of the lesion. Results: Final sample of 40 patients, 40 swabs and 40 biopsies. Of the 40 swabs, 32 were positive and 08 negative; among biopsies, 30 were positive and 10 negative. Fifteen different types of microorganisms were found, with 02 (13.3%) Gram positive and 13 Gram negative bacteria. Of the bacteria found, the most frequent Gram positive was Staphylococcus aureus (8.06%) producing beta-lactamase and the most common negative Gram was Pseudomonas aeruginous (40.3%). Conclusion: From this study it was possible to identify the main microorganisms according to the etiology of the lesion for the treatment of infections.